INTENSI PENGGUNAAN ELECTRONIC WALLET GENERASI MILLENIAL PADA TIGA STARTUP “UNICORN” INDONESIA BERDASARKAN MODIFIKASI TAM - Lusia Tria Hatmanti Hutami (Jurnal Manajemen, 2018)
The millennial generation is the future which preferable and fluent with technology sophistication, technology in this paper focuses on payment system through the electronic wallet. The aims of this research have tested the influence of factors based on modified TAM theory. This testing used a regression model which distributed online. The total of the sample that meets the criteria was 210 respondents. Perceived usefulness, perceived ease of use and subjective norm were proven positively influence the intention of using the electronic wallet in an online buying. Perceived ease of use gained the highest impact toward the intention of using electronic wallet than the others factor. Therefore, startup businessman should provide innovation in a payment system which easies to understand so that the customer more interested in using electronic wallet service.